2020
DOI: 10.1038/s41598-020-77519-8
|View full text |Cite
|
Sign up to set email alerts
|

Supporting elimination of lymphatic filariasis in Samoa by predicting locations of residual infection using machine learning and geostatistics

Abstract: The global elimination of lymphatic filariasis (LF) is a major focus of the World Health Organization. One key challenge is locating residual infections that can perpetuate the transmission cycle. We show how a targeted sampling strategy using predictions from a geospatial model, combining random forests and geostatistics, can improve the sampling efficiency for identifying locations with high infection prevalence. Predictions were made based on the household locations of infected persons identified from previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…household members, adult males) and high prevalence locations. Heterogeneity (clustering) observed between and within PSUs and households also leads to consideration of different sampling strategies including spatially explicit sampling and prediction [ 42 ], adaptive or snowball sampling [ 43 ], the use of markers that are potentially more sensitive than Ag or Mf (e.g. anti-filarial antibodies [ 27 , 41 , 44 ]), molecular xenomonitoring of mosquitoes [ 45 48 ], or combinations of these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…household members, adult males) and high prevalence locations. Heterogeneity (clustering) observed between and within PSUs and households also leads to consideration of different sampling strategies including spatially explicit sampling and prediction [ 42 ], adaptive or snowball sampling [ 43 ], the use of markers that are potentially more sensitive than Ag or Mf (e.g. anti-filarial antibodies [ 27 , 41 , 44 ]), molecular xenomonitoring of mosquitoes [ 45 48 ], or combinations of these.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up surveys will assess the impact of two rounds of triple-drug MDA on transmission. Other surveillance strategies being investigated in Samoa include spatial sampling strategies [ 42 ] and molecular xenomonitoring.…”
Section: Discussionmentioning
confidence: 99%
“…household members, adult males) and high prevalence locations. Heterogeneity (clustering) observed between and within PSUs and households also leads to consideration of different sampling strategies including spatially explicit sampling and prediction [43], adaptive or snowball sampling [44], and the use of markers that are potentially more sensitive than Ag or Mf e.g. anti-filarial antibodies [32,42,45], molecular xenomonitoring of mosquitoes [46-49], or combinations of these.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up surveys will assess the impact of two rounds of triple-drug MDA on transmission. Other surveillance strategies being investigated in Samoa include spatial sampling strategies [43] and molecular xenomonitoring.…”
Section: Mda Participation In Ag and Mf Positive Personsmentioning
confidence: 99%
“…5,7 A series of studies has also demonstrated persistent transmission of LF in some of these countries, and research partners have provided continuous feedback to relevant health ministries/departments to emphasize the critical importance of intensifying and sustaining LF interventions to relevant health ministries/departments. [8][9][10][11][12][13][14][15][16] All these factors combined have made the development of a new strategy to accelerate LF elimination crucial.…”
Section: Lymphatic Filariasis Situation In the Pacific Before The Int...mentioning
confidence: 99%